Clinical chest ultrasound from the ICU to the bronchoscopy suite - Bolliger, Christoph T.; Herth, Felix; Mayo, Paul H.; Miyazawa, Teruomi; Beamis, John F. (Karger, 2009)
Pleural effusions, left and right heart dysfunction, mediastinal nodal pathology, and pulmonary embolism are just a few of the many thoracic diseases which can be diagnosed with the help of ultrasound techniques! Chest sonography has become an established procedure in the stepwise imaging diagnosis of pulmonary, cardiac, and pleural disease. It is the method of choice for many diseases and allows the investigator to make an unequivocal diagnosis without exposing the patient to costly and stressful procedures. This book, volume 37 in the well-known Progress in Respiratory Research series, presents the state of the art in clinical chest ultrasonography. As implied by its title, it covers all aspects of ultrasound involving the chest, at the same time differentiating between routine and emergency procedures. Basic elements such as indications, investigational techniques and imaging artifacts are detailed in separate chapters. The large number of excellent illustrations and the compact text provide concise and easy-to-assimilate information about the diagnostic procedure. Apart from the printed still pictures, the book comes with a complimentary online repository containing a variety of key videos. Each chapter presents an autonomous concise overview of indications, methods, diagnoses and pitfalls and can be used as a systematic review. It is written by leading experts as a guide by clinicians for clinicians and is a must for physicians, pulmonologists, intensivists, as well as all doctors with an interest in chest medicine
online supplementary material
Keywords: Chest - Ultrasonic imaging; Thoracic Diseases - ultrasonography; Thorax - ultrasonography; Respiratory System; Cardiovascular System; Intensive Care; Internal Medicine; Ultrasound; Chest -- Ultrasonic imaging; Thoracic Diseases -- ultrasonography; Thorax -- ultrasonography; Ultraschalldiagnostik; Brustkorb; Krankheit; Brustorgan; Aufsatzsammlung